Effects of messenger RNA structure and other translational control mechanisms on major histocompatibility complex‐I mediated antigen presentation. (26th September 2014) - Murat, Pierre; Tellam, Judy
Abstract : Effective T‐cell surveillance of antigen‐presenting cells is dependent on the expression of an array of antigenic peptides bound to major histocompatibility complex (MHC) class I (MHC‐I) or class II (MHC‐II) molecules . Pathogens co‐evolving with their hosts exploit crucial translational regulatory mechanisms in order to evade host immune recognition and thereby sustain their infection. Evasion strategies that downregulate viral protein synthesis and thereby restrict antigen presentation to cytotoxic T‐cells through the endogenous MHC‐I pathway have been implicated in the pathogenesis of viral‐associated malignancies. An understanding of the mechanisms by which messenger RNA (mRNA) structure modulates both viral mRNA translation and the antigen processing machinery to escape immune surveillance, will stimulate the development of alternative therapeutic strategies focused on RNA‐directed drugs designed to enhance immune responses against infected cells. In this review, we discuss regulatory aspects of the MHC‐I pathway and summarize current knowledge of the role attributed by mRNA structure and other translational regulatory mechanisms in immune evasion. In particular we highlight the impact of recently identified G‐quadruplex structures within virally encoded transcripts as unique regulatory signals for translational control and antigen presentation. WIREs RNA 2015, 6:157–171. doi: 10.1002/wrna.1262 This article is categorized under: RNA Structure and Dynamics > Influence of RNA Structure in Biological Systems Translation > Translation Regulation